(3ChVM QeR Ydi fXe GdcfRs - (3Ydj Hf eMeO Hf Ydj, ef hdO SYO GHf YHGOI GdNRQLj, fhQ GdOjf GHf ZGfe , (B1014 (3g` s; (3MGaX GdOjf CHh GdHQcGJ YHO Gddg Hf CMeO Hf eMehO GdfSaj,J (B710 (3g` s
(3ChdgG (B:s
(3hHYO agPG ChVM QeR Ydi fXe GdcfR ddYdGeI GdTgjQ HGHf GdaUjM bUOJ ajg JeGe GdJhVjM heRjO GdJgPjH hGdJfbjM s
(3BNQgG (B:s
(3hGddg SHMGfg hJYGdi CYde jJdhg cJGH GdfcGM s
(3GdfSNI HgG MhGTs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B67 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B32s
(3cTa GdXfhf (B- (3GdLRA (B2 - (3U (B1515 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1516s
Keywords: (3Gdabg GdMfajs